A novel LTCC electrochemical cell construction and characterization: A detection compartment for portable devices - Pesquero, Naira Canevarolo [UNESP]; Gongora-Rubio, Mário Ricardo; Yamanaka, Hideko [UNESP] (Royal Society of Chemistry (RSC), 2013)
In this work we described for the first time the construction of a 25 μL electrochemical cell from low temperature co-fired ceramic (LTCC) material and carbon screen-printed electrode applicable in portable devices. Firstly, a carbon screen-printed electrode was prepared and characterized by cyclic voltammetry and scanning electron microscopy. Afterwards carbon polymeric film and metal pastes were dropped into the LTCC cell cavities in order to determine the device electrodes, and this arrangement was also electrochemically characterized. The great advantage of this promising device is the simple construction method and its widespread applicability in reusable portable devices. © 2013 The Royal Society of Chemistry.